ANALISIS KESALAHAN MAHASISWA DALAM MENYELESAIKAN SOAL CERITA BERDASARKAN METODE NEWMANN - Bulu, Vera Rosalina (Journal of Honai Math, 2020)
This Qualitative study aimed to describe the students the mistakes in solving the problems related to cubes and cuboid topics based on Newmann's procedures. To gather the data, three students of primary school teacher department in a university in Kupang, Indonesia, with a high, moderate and low problem – solving skills were chosen to be analyzed further using descriptive method. The result showed that the students with a high problem – solving skill were doing wrong in writing the final answer due to an incomplete understanding of cube and cuboid. The students with a moderate problem – solving skill were doing mistake in transforming the word problems into mathematical expression since the students were not accustomed to do non – routine problem. Furthermore, the students with the low problem – solving skills were doing mistakes in transforming word problems into a mathematical expression, during the process and writing the final answer. The mistake was emerged due to students’ inability to understand the problems and incomplete understanding of the concept of cube and cuboid.